ANALISIS KESULITAN PEMBELAJARAN MATA KULIAH MENGGAMBAR TEKNIK 1 PADA MAHASISWA PTB UNJ ANGKATAN 2022 - Mohammad Ragil Reynaldi (ADISAM PUBLISHER, 2025)
In the 21st century, learners are not merely recipients of information, educators are not solely facilitators of learning, and learning resources encompass more than materials for the exchange of knowledge and skills. However, in practice, eflective implementation of learning is not straightforward. Engineering Drawing 1 is one of the compulsory foundational courses in the early semester of the Building Engineering Education Program at Universitas Negeri Jakarta. One of the learning objectives of this course is mastery of CAD (Computer Aided Design). Nevertheless, various factors contribute to challenges in achieving the course objectives. The encountered difficulties are divided into two factors: internal factors including Motivation, Interest, Attitude, and Concentration, and external factors including Facilities and Infrastructure, Learning Materials or Media, Economic, and Environment. This research adopts a descriptive analysis approach focusing on quantitative aspects. The study was conducted on March 25-26, 2024. The research subjects consisted of 35 students from the 2022 cohort of the Building Engineering Education Program. The questionnaire results indicate that external factors are predominant, with material aspects accounting for 31.4% and economic aspects for 45.7%. Although internal and external factors do not show significant results individually, both still influence the learning of Engineering Drawing 1. Therefore, it can be concluded that further analysis is needed regarding the learning difficulties of Engineering Drawing 1 in the Building Engineering Education Program at Universitas Negeri Jakarta